2021 IEEE Symposium Series on Computational Intelligence (SSCI) 2021
DOI: 10.1109/ssci50451.2021.9659905
|View full text |Cite
|
Sign up to set email alerts
|

Clustering in Recurrent Neural Networks for Micro-Segmentation using Spending Personality

Abstract: Customer segmentation has long been a productive field in banking. However, with new approaches to traditional problems come new opportunities. Fine-grained customer segments are notoriously elusive and one method of obtaining them is through feature extraction. It is possible to assign coefficients of standard personality traits to financial transaction classes aggregated over time. However, we have found that the clusters formed are not sufficiently discriminatory for micro-segmentation. In a novel approach,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…This is consistent with the high affinity of conscientious spenders towards residential mortgages [17]. It is compelling to expand the notion of personality traits from spending to wealth creation, i.e., to base personal investment advice on historical spending behaviour [18,19].…”
Section: Related Workmentioning
confidence: 54%
“…This is consistent with the high affinity of conscientious spenders towards residential mortgages [17]. It is compelling to expand the notion of personality traits from spending to wealth creation, i.e., to base personal investment advice on historical spending behaviour [18,19].…”
Section: Related Workmentioning
confidence: 54%
“…We have previously developed a three-node RNN that predicts customer personalities from an input vector of their classified financial transactions [3]. This input vector consists of six annual time steps, each consisting of 97 transaction classes; the values in each time step add up to one and are the fraction of a customer's annual spending per transaction category.…”
Section: Methodsmentioning
confidence: 99%
“…Although they achieved only a modest predictive accuracy, a subsequent study found that spending patterns over time expose salient information that is obscured in non-temporal form [13]; the authors in this study used the same personality model, but added temporal patterns such as variability of the amount, persistence of the category in time, and burstiness-the intermittent changes in frequency of an event. Recurrent neural networks (RNNs) are able to extract this salient information when predicting personality traits from financial transactions [3]. In, [14], we gained an understanding of these extracted features by interpreting the dynamics of the RNN state space through a set of attractors.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that our fundamentally sound algorithm was able to imbue specific characteristic behaviours into our agents' policies. In future work, we intend to use this algorithm to develop a set of financial advisors that will optimize individual customers' investment portfolios according to their individual spending personalities [24]. While maximising portfolio values, these agents may prefer, e.g., property investments over crypto currencies which are analogous to right turns and left turns in our toy problem.…”
Section: Conclusion and Direction For Future Workmentioning
confidence: 99%